The effect of fluoride exposure on the load-deflection properties of superelastic nickel-titanium-based orthodontic archwires - Ahrari Farzaneh; Ramazanzadeh Barat-Ali; Sabzevari Berahman; Ahrari Ali (Sciendo, 2012)
Background: It has been demonstrated that fluoride prophylactic agents may cause hydrogen absorption in NiTi wires and degrade their mechanical properties.